Genome-wide association study identifies locus at chromosome 2q32.1 associated with syncope and collapse. Issue 1 (3rd May 2019) - Hadji-Turdeghal, Katra; Andreasen, Laura; Hagen, Christian M; Ahlberg, Gustav; Ghouse, Jonas; Bækvad-Hansen, Marie; Bybjerg-Grauholm, Jonas; Hougaard, David M; Hedley, Paula; Haunsø, Stig; Svendsen, Jesper H; Kanters, Jørgen K; et al.
Abstract: Aims: Syncope is a common condition associated with frequent hospitalization or visits to the emergency department. Family aggregation and twin studies have shown that syncope has a heritable component. We investigated whether common genetic variants predispose to syncope and collapse. Methods and results: We used genome-wide association data on syncope on 408 961 individuals with European ancestry from the UK Biobank study. In a replication study, we used the Integrative Psychiatric Research Consortium (iPSYCH) cohort ( n  = 86 189), to investigate the risk of incident syncope stratified by genotype carrier status. We report on a genome-wide significant locus located on chromosome 2q32.1 [odds ratio = 1.13, 95% confidence interval (CI) 1.10–1.17, P  = 5.8 × 10 −15 ], with lead single nucleotide polymorphism rs12465214 in proximity to the gene zinc finger protein 804a ( ZNF804A ). This association was also shown in the iPSYCH cohort, where homozygous carriers of the C allele conferred an increased hazard ratio (1.30, 95% CI 1.15–1.46, P  = 1.68 × 10 −5 ) of incident syncope. Quantitative polymerase chain reaction analysis showed ZNF804A to be expressed most abundantly in brain tissue. Conclusion: We identified a genome-wide significant locus (rs12465214) associated with syncope and collapse. The association was replicated in an independent cohort. This is the first genome-wide association study to associate a locus with syncope and collapse.